Development and validation of a reversed-phase HPLC method for analysis of tetrahydrozoline hydrochloride in eye drop formulations - Fuad Al-Rimawi; Wahbeh Zareer; Salah Rabie; Mazen Quod (Elsevier, 2012)
A simple, precise, accurate, and stability-indicating method is developed and validated for analysis of tetrahydrozoline hydrochloride in eye drop formulations. Separation was achieved on a reversed-phase C8 column (125Â mmÃ4.6Â mm i.d., 5Â Î¼m) using a mobile phase consisting of acetonitrile/phosphate buffer of pH 3.0 (20:80, v/v) at a flow rate of 1.0Â mL/min and UV detection at 240Â nm. This method is validated according to United States Pharmacopeia requirements for new methods, which include accuracy, precision, selectivity, robustness, and linearity and range. This method shows enough selectivity, accuracy, precision, and linearity and range to satisfy Federal Drug Administration/International Conference on Harmonization regulatory requirements. The current method demonstrates good linearity over the range of 0.025â0.075Â mg/mL of tetrahydrozoline with r2 0.999. The average recovery of the method is 100.8% with a relative standard deviation of 0.47%. The degree of reproducibility of the results obtained as a result of small deliberate variations in the method parameters and by changing analytical operators has proven that the method is robust and rugged. Keywords: Tetrahydrozoline hydrochloride, Validation, Precision, Accuracy, Linearity